In search of "Kynde Knowynge" : Piers Plowman and the origin of allegory - Kasten, Madeleine (Costerus ;, 2007)
Readers today no longer relish sustained allegorical narratives the way they did in the Middle Ages, when the art of 'other-speaking' was as dominant in poetic discourse as it was elsewhere. Yet we live in an age which, following the postmodernist dictum that any sign can only refer to other signs, has declared all language liable to the 'allegorical condition'. This paradox has led the author to question the epistemological assumptions underlying allegories composed in an era which, conversely, favoured the oblique form of expression while professing its belief in the divine Logos as the ultim.